Nurses' performance in relation to the prevention of penile cancer in Primary Health Care: A review of the scope of the literature (Research, Society and Development, 2021)
Penile cancer is a rare type, with a high incidence in men of the third age, however, it can be affected in younger people. The disease affects individuals of low social level, with poor hygienic habits, having phimosis as the main risk factor and often associated with human papillomavirus (HPV). The delay in seeking medical help, late treatment in most cases, penile cancer will have to undergo surgery, with total or partial penectomy and metastasis often occurring, an alternative that affects the psychological, physical and human health of men and women. the whole family. Most have heard about penile cancer and know that intimate hygiene with soap and water, circumcision, and condom use are the most effective means of prevention. This is a bibliographic research with a qualitative approach and descriptive character, which aimed to understand nurses' practices and knowledge in the prevention of penis cancer in Primary Health Care. The results indicate that health education is one of the main tools for the prevention of penile cancer. We conclude that health promotion is a relevant strategy in the face of breast cancer and that nurses, when identifying vulnerable groups, can establish preventive measures and health education for those who are at risk of the disease.